The wicked mate the antarctic diary of Victor Campbell ; an account of the Northern Party on Captain Scott's last expedition from the original manuscript in the Queen Elizabeth II Library, Memorial University of Newfoundland - Campbell, Victor (Bluntisham Books u.a., 1988)
Annotated diary of Lieutenant Victor Campbell, leader of the Northern party of R.F. Scott's British Antarctic Expedition (1910-'13), who explored the coast of King Edward VII Land and returned successfully. Includes a biography of Campbell, maps, photographs, sketches and references.